Structural, electrical and magnetic properties of substituted pyrochlore oxide nanoparticles synthesized by the co-precipitation method: Substituted pyrochlore oxide - Khanvilkar, M.B.; Nikumbh, A.K.; Patange, S.M.; Pawar, R.A.; Karale, N.J.; Nighot, D.V.; Nagwade, P.A.; Sangale, M.D.; Gugale, G.S. (Physics and Chemistry of Solid State, 2021)
Five substituted pyrochlore nanooxides such as Nd1.9Ho0.1Zr1.8Ce0.2O7, La1.95Ce0.05Zr0.29Ce1.71O7, Y1.79Pr0.21Ru1.99Pr0.01O7, Dy1.9Yb0.1Mn1.93Cu0.07O7 and Dy1.99Sr0.01Sn2O7 were synthesized by coprecipitation method. These precursors were monitored by thermal studies (TGA-DTA). The prepared nanosized substituted pyrochlore oxides were characterized by EDS, XRD, SEM, TEM, d. c. electrical conductivity, Thermoelectric power, Hall effect measurement, dielectric properties and magnetization measurements. XRD confirmed the formation of a single phase crystalline substituted pyrochlores with a cubic nature of nanoparticles. All substituted compounds were adopted a stable pyrochlore structure with rA3+/rB4+ = 1.395 except La1.95Ce0.05Zr0.29Ce1.71O7 compound, which has rA3+/rB4+ = 1.175 indicate disorder pyrochlore structure (i.e. fluorite structure). The temperature dependence of d. c. electrical conductivity for all substituted pyrochlores exhibits two distinct slopes with a break. This discontinuity can be attributed to extrinsic to intrinsic semiconducting properties. The thermoelectric power and Hall effect measurements for all compounds were confirmed the p-type semiconductivity except Y1.79Pr0.21Ru1.99Pr0.01O7 compound and which showed n-type semiconductivity. The dielectric constant (ε’) and dielectric loss (tan δ) i. e dissipation factor decreases with an increase in frequencies and reaching constant at particular frequencies. The applied field dependence of magnetization curve at room temperature (300 K) for Nd1.9Ho0.1Zr1.8Ce0.2O7, Y1.79Pr0.21Ru1.99Pr0.01O7 and Dy1.9Yb0.1Mn1.93Cu0.07O7, showed hysteresis loop with a small kink around the origin and which can be attributed to small but definite ferromagnetic ordering along with significant paramagnetic and superparamagnetic components. The magnetization at 2K showed a clear hysteresis loop for Dy1.9Yb0.1Mn1.93Cu0.07O7 and Dy1.99Sr0.01Sn2O7 pyrochlores are soft (weak) ferromagnets.